Heavy Metals Pollution in the Bed Load Sediments of the Brantas River in Batu City - Abdalnasser A M Khalifa; Arief Rachmansyah; Amin Setyo Leksono (Indonesian Journal of Environment and Sustainable Development, 2022)
Aim to Evaluation the contamination levels of heavy metals As, Cr, Zn, and Pb upstream of Brantas River using IP (Inductively Coupled Plasma) to measure heavy metal and identify the use of synthetic pesticides and fertilizer and Recommend strategies to reduce contamination of heavy metal, where were collected16 samples sediment from two different branches river, each location has different grains size 0.063 µm and 0.200 µm. The increasing trend of metals was observed in sediments of the Grain size 0.200 µm As‚ Pb‚ Zn‚ Cr respectively and in the Grain size 0.063 µm As‚ Cr‚ Zn‚ Pb in the river one and for the river two in the Grain size 0.200 µm. The increasing trend of metals was observed in sediments Pb‚ As‚ Cr, Zn and the Grain size 0.063 As‚ Zn‚ Pb‚ Cr, which means the concentration levels in sediment all the metals in the Grain size 0.200 µm in river one and river two higher than safe values and in grain size 0.063 µm lower than safe values. This is what was shown in the Assessment of the degree of pollution in sediments using (EF), (PLI), (Igeo) and (CF). Keywords: heavy metal, Sediment, Evaluate Contamination